Investigation of the Effects of Substituents and Various Solvents on UV-Visible Spectra of 5-(Quinolinylmethylene)barbituric Acid Derivatives - Canlica, Mevlude; Beker, H. Kerim; Akinci, Alper; Kaban, Seniz (ASIAN JOURNAL OF CHEMISTRY, 2009)
The effects of substituents and solvents on the UV-visible spectra of 5-(quinolinylmethylene)barbituric acid derivatives have been investigated.
Keywords: Barbituric acid; Thiobarbituric acid; Substituent effect; Solvent polarity effect; Chemistry